Self-assembling functional programmable protein array for studying protein-protein interactions in malaria parasites (2018)
Background: Plasmodium vivax is the most widespread malarial species, causing significant morbidity worldwide. Knowledge is limited regarding the molecular mechanism of invasion due to the lack of a continuous in vitro culture system for these species. Since protein-protein and host-cell interactions play an essential role in the microorganism’s invasion and replication, elucidating protein function during invasion is critical when developing more effective control methods. Nucleic acid programmable protein array (NAPPA) has thus become a suitable technology for studying protein-protein and host-protein interactions since producing proteins through the in vitro transcription/translation (IVTT) method overcomes most of the drawbacks encountered to date, such as heterologous protein production, stability and purification. Results: Twenty P. vivax proteins on merozoite surface or in secretory organelles were selected and successfully cloned using gateway technology. Most constructs were displayed in the array expressed in situ, using the IVTT method. The Pv12 protein was used as bait for evaluating array functionality and co-expressed with P. vivax cDNA display in the array. It was found that Pv12 interacted with Pv41 (as previously described), as well as PvMSP142kDa, PvRBP1a, PvMSP8 and PvRAP1. Conclusions: NAPPA is a high-performance technique enabling co-expression of bait and query in situ, thereby enabling interactions to be analysed rapidly and reproducibly. It offers a fresh alternative for studying protein-protein and ligand-receptor interactions regarding a parasite which is difficult to cultivate (i.e. P. vivax).